A Lean Six Sigma program in higher education. Issue 9 (5th October 2015) - Svensson, Carsten; Antony, Jiju; Ba-Essa, Mohamed; Bakhsh, Majed; Albliwi, Saja
Abstract : Purpose: – The purpose of this paper is to contribute to the body of Lean Six Sigma (LSS) knowledge within the field of higher education institutions. The paper will review the initial phase of an implementation and highlight future challenges of applying the LSS method in a complex transactional environment. Design/methodology/approach: – The observations presented in this paper originate from rolling out a large LSS implementation at a recently established university. The paper is supported with secondary data from literature. Findings: – The implementation of LSS methodology at King Abdullah University of Science and Technology has resulted in improvements in business processes and efficiency. This has been achieved through project execution and training programs. Approximately 350 staff members have completed awareness training, 50 yellow belts and 150 green belts have been trained, and the first round of seven black belts have completed training of which two have completed certification. Research limitations/implications: – This paper is based on an empirical study of a single instance and the authors' experiences as practitioners. Originality/value: – This paper is the first description of what is believed to be one of the largest implementations of LSS in higher education.